2017
DOI: 10.5539/ijps.v9n4p65
|View full text |Cite
|
Sign up to set email alerts
|

Maladaptive Perfectionism and Psychological Distress: The Mediating Role of Resilience and Trait Emotional Intelligence

Abstract: University students experience significantly high levels of psychological distress. Such distress has been related to depression and anxiety, which in turn have been related to low resilience and low trait emotional intelligence, and also to maladaptive perfectionism. However, no current research has investigated maladaptive perfectionism's relationship with a more general psychological distress experienced by university students. Therefore, the current study investigated associations among maladaptive perfect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 34 publications
0
10
0
1
Order By: Relevance
“…It should be considered, though, that requests for increased preparation and exemplars of interviews may, in fact, be indicative of perfectionism and the associated anxiety around performance. University students in competitive programs, such as psychology, are well recognised as experiencing levels of perfectionism that can impair learning (Christman, ; Rozental et al, ; Sheppard & Hicks, )—this need for perfectionism must be considered in scaffolding and supporting students in what are to them, novel, and thus potentially anxiety‐provoking learning environments.…”
Section: Discussionmentioning
confidence: 99%
“…It should be considered, though, that requests for increased preparation and exemplars of interviews may, in fact, be indicative of perfectionism and the associated anxiety around performance. University students in competitive programs, such as psychology, are well recognised as experiencing levels of perfectionism that can impair learning (Christman, ; Rozental et al, ; Sheppard & Hicks, )—this need for perfectionism must be considered in scaffolding and supporting students in what are to them, novel, and thus potentially anxiety‐provoking learning environments.…”
Section: Discussionmentioning
confidence: 99%
“…These observations may have been statistically significant with a larger sample size. Avoidance coping can contribute to anxiety and depression ( Tan-Kristanto and Kiropoulos, 2015 ), and perfectionist tendencies are associated with high levels of psychological distress ( Sheppard and Hicks, 2017 ). On the other hand, a detached coping style positively correlates with optimism and resilience ( Gupta et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, getting involved in some source of income could hamper with their studies, leading to under-preparation and Phobia during exams. In fact, a study on university students by Smith et al identified financial condition as a significant factor contributing to increased rates of dropouts among the mentioned population [27].…”
Section: Discussionmentioning
confidence: 99%
“…Attending classes regularly could mean a greater understanding and knowledge of the subject, and thereby eliminating any fear associated with it or examinations. Sheppard and Hicks in their study showed that maladaptive perfectionism has been identified as a mutual characteristic among students that leads to identified situations such as depression and anxiety [28].…”
Section: Discussionmentioning
confidence: 99%